Clinical Spectrum of Emergency Presentations in End-Stage Kidney Disease Patients on Hemodialysis: Experience from a Tertiary Care Center in Pakistan - Aman, Babar; Raza, Ali; Zulfiqar, Warda; Sohail, Muhammad Waheed; Khan, Fayaz (Indus Journal of Bioscience Research, 2025)
Background: End-stage kidney disease (ESKD) is associated with high morbidity and frequent emergency department (ED) utilization due to acute complications. This study aimed to evaluate the clinical profile and causes of ED visits among ESKD patients undergoing maintenance hemodialysis at a tertiary nephrology center in Peshawar, Pakistan. Methods: A facility-based, cross-sectional study was conducted at Khyber Teaching Hospital from November 2024 to March 2025. A total of 384 adult patients on maintenance hemodialysis who presented to the ED were enrolled. Data were collected using a structured proforma and analyzed using SPSS v24. Results: Most patients were male (57.8%) and hypertensive (88.0%), with diabetes mellitus (50.5%) also common. The majority were on twice-weekly in-center dialysis using arteriovenous fistulae. Infection-related complications were the leading cause of ED visits (68.5%), with respiratory tract and access-related infections most common. Electrolyte imbalances, pulmonary edema, and cardiovascular emergencies were also frequent. Catheter use and suboptimal dialysis were associated with increased acute presentations. Conclusion: ESKD patients face a high burden of preventable complications. Improved outpatient monitoring, individualized dialysis plans, and better infection control measures are essential to reduce ED utilization and improve outcomes in this population.